Beneficial Effects of Methylene Blue on the Acute Phase of Corrosive Esophageal Burn in Rats - Kilincaslan, Huseyin; Karatepe, Hande Ozgun; Kilic, Elif; Aydogdu, Ibrahim; Gedik, Ahmet Hakan; Olgac, Vakur; Kucukkoc, Mehmet (European Journal of Pediatric Surgery, 2015)
Introduction The aim of the article is to investigate the beneficial effects of methylene blue (MB) on the acute phase of experimental corrosive esophageal burns.Materials and Methods A total of 21 male Sprague-Dawley rats were allocated into three groups with an equal number in each group. In Group 1 (control), the esophageal lumen was irrigated with saline. In Groups 2 (untreated) and 3 (MB treatment), the distal esophagus was burned with 30% NaOH solution. In Group 3, MB was applied locally on the distal esophageal lumen (30 mg/kg) 90 minutes after the burn. In all the groups, animals were humanely killed at the end of the 7th day. Distal esophageal specimens were obtained for histopathological and biochemical examinations.Results MB increased the tissue superoxide dismutase levels and the total antioxidant status, whereas it decreased the levels of the total oxidant status with significant attenuation of histopathological damage.Conclusion MB might have reduced the tissue damage in corrosive esophagitis because of its antioxidant effects.
Keywords: corrosive esophageal burn; methylene blue; total oxidant status; total antioxidant status